Students’ Difficulties In Comprehending English Reading Text At SMP Methodist 9 Medan - Millenia, Shella; Pane, Isli Iriani Indiah (Universitas Negeri Medan, 2023)
This study aimed to discover the difficulties which the Eighth Grade Students of SMP Methodist 9 Medan face in comprehending English reading text and investigate the factors which cause the difficulties. This study used descriptive qualitative research design. The subjects of this study was one class of Eighth Grade students of SMP Methodist 9 Medan. This study used Reading Comprehension Test and Interview in collecting the data. The findings of this study showed that there were a total of 332 difficulties experienced by students in comprehending English reading text, they are (1) Students have a total of 67 difficulties in Determining Main Idea with a percentage of 20.2%. (2) Students have a total of 58 difficulties in Finding Detail Information with a percentage of 17.5%. (3) Students have a total of 62 difficulties in Making Inference with a percentage of 18.7%. (4) Students have a total of 63 difficulties in Identifying Reference with a percentage of 18.9%. (5) Students have a total of 82 difficulties in Understanding Vocabulary with a percentage of 24.7%. Meanwhile, factors of students’ difficulties in reading comprehension, namely: limited vocabulary knowledge, lack of fluency, lack of familiarity with the subject matter, the difficulty level of the text (readability), inadequate use of effective reading strategies, weak verbal reasoning, problems with processing information, and problems in recalling information after reading.